CANVAS model: what does change with IA and RPA? (Costos y Gestión, 2025)
Advances in the applications of artificial intelligence (AI) and robotic process automation (RPA) can impact changes in the formation of business models.Since CANVAS is a model of wide adoption and application in organizations, it is important to evaluate the degree of impact it can have in its 9 blocks.The main objective of the presentation is to evaluate, analyze and validate the possibilities of changes in the dynamics of each of the blocks, given the impact of advances in AI and RPA.The complementary objective is focused on the analysis of the possible alteration of the design of the CANVAS Model, as a result of the prominence of AI and RPA in the operation, dynamics and sustainability of businesses in the near future.  Is it possible that new blocks should be added? Will any of the current ones disappear or lose prominence? Can the value dynamics be altered by the changes brought about by AI and RPA?This is an article of reflection and critical analysis, about the model in question. Therefore, a non-empirical work will be developed, with a qualitative approach and an exploratory scope.
Keywords: CANVAS; artificial intelligence; IA; RPA; disruption